NATURAL PESTICIDES FROM SEEDS OF CHIRIMOYA (Annona cherimolia Mill.) AND GUANABANA (Annona muricata L.) - Rivera C., D. (2010)
Seeds of chirimoya and guanabana from the communities of Cumbe and Callahuanca - Yauyos, Lima were analyzed. The extraction of natural toxic was realized using ethanol as the optimal solvent, after several solvent tests, phytochemicals analysis identified :saponins, coumarins, tannins, quinones and essential oils, mostly castor oil which was confirmed by FTIR spectra. Qualitative analysis results identified: PO4(3-), AsO4(3-) and others. Toxicological tests extracts applied on larvae and fruit flies finding levels of mortality as 88% to 94% on chirimoyas and guanabanas respectively.